2007
DOI: 10.1118/1.2713427
|View full text |Cite
|
Sign up to set email alerts
|

The impact of breathing motion versus heterogeneity effects in lung cancer treatment planning

Abstract: The purpose of this study is to investigate the effects of tissue heterogeneity and breathing-induced motion/deformation on conformal treatment planning for pulmonary tumors and to compare the magnitude and the clinical importance of changes induced by these effects. Treatment planning scans were acquired at normal exhale/inhale breathing states for fifteen patients. The internal target volume (ITV) was defined as the union of exhale and inhale gross tumor volumes uniformly expanded by 5 mm. Anterior/posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…The motivation is clear: The less breathing phases are required in the accumulation process, the less images have to be acquired and the less computational time is needed for the 4D dose calculation. In related studies in literature, the number of phases can be found to vary mainly between two (endexpiration and end-inspiration) [10,41] and ten phases (e.g. [42,12]).…”
Section: Discussionmentioning
confidence: 98%
“…The motivation is clear: The less breathing phases are required in the accumulation process, the less images have to be acquired and the less computational time is needed for the 4D dose calculation. In related studies in literature, the number of phases can be found to vary mainly between two (endexpiration and end-inspiration) [10,41] and ten phases (e.g. [42,12]).…”
Section: Discussionmentioning
confidence: 98%
“…It is worth stressing that these results were obtained considering constant lung density over the breathing cycle. Recent studies show that such approximation results in minor effects if compared to motion and heterogeneities correction (20, 35). Normal lung DVHs illustrate that tracking has a dosimetric advantage vs. gating, at least in a large motion case.…”
Section: Resultsmentioning
confidence: 99%
“…Maximum anterior-posterior (AP) expansion of the chest wall applies to motion studies in the lung (20). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have investigated the effect of motion in radiotherapy and shown that it can be a large source of error between planned and delivered dose distributions if it is not accounted for (Bortfeld et al 2002, Court et al 2008, Flampouri et al 2006, Ford et al 2003, Jiang et al 2003, Langen and Jones 2001, Lujan et al 2003, Rosu et al 2007, Schaefer et al 2004, Seco et al 2007, 2008, Shimizu et al 2001, Yu et al 1998). The use of four-dimensional computed tomography (4D-CT) and periodic portal imaging has allowed the nature of the target volume to be seen both over the course of a breathing cycle and throughout a course of radiotherapy, respectively (Keall 2004, Keall et al 2004, Liu et al 2007, Low et al 2003, Maxim et al 2007, Pan et al 2004, Rietzel et al 2005a, 2005b, Rosu et al 2006, Vedam et al 2003).…”
Section: Introductionmentioning
confidence: 99%